Prediction of mechanical ventilation outcome by early abdominal-visceral-blood-flow-and-function score in critically ill patients after cardiopulmonary bypass in the ICU: A prospective observational study - Chaofu Yue; Longxiang Su; Jun Wang; Na Cui; Yuankai Zhou; Wei Cheng; Bo Tang; Xi Rui; Huaiwu He; Yun Long (Journal of Intensive Medicine, 2024)
Background: Abdominal organs are important organs that sense and respond to ischemia and hypoxia, but there are few evaluation methods.We use ultrasonography to evaluate abdominal organ function and blood flow in patients with mechanical ventilation (MV) after cardiopulmonary bypass and to obtain a semiquantitative score for abdominal organ function and blood flow. Methods: Patients with cardiopulmonary bypass in the Critical Care Department of Peking Union Medical College Hospital in China from March to July 2021 were enrolled in this prospective observational study. The correlation of the abdominal-visceral-blood-flow-and-function score (AVBFS) with the duration of MV, number of days spent in the intensive care unit (ICU), acute physiology and chronic health evaluation II (APACHE-II), sequential organ failure assessment (SOFA), lactate, epinephrine, and norepinephrine use was analyzed, and the results were used to assess the predictive value of the receiver operating characteristic curve (ROC) regression analysis score for the duration of MV. Results: Of the 92 patients who underwent cardiopulmonary bypass, 41 were finally included. The AVBFS were significantly correlated with the duration of MV, number of days spent in the ICU, APACHE-II score, SOFA score, and norepinephrine use time. The AVBFS in a group of patients using ventilators ≥36 h were significantly higher than those obtained for a group of patients using ventilators <36 h (P <0.05). The evaluation results for the AVBFS at 0-12 h after ICU admission were as follows: area under the ROC curve (AUC)=0.876 (95% confidence interval [CI]: 0.767 to 0.984), cut-off value=2.5, specificity=0.842, and sensitivity=0.773. Conclusions: Abdominal visceral organ function and blood perfusion can be used to evaluate gastrointestinal function. It is related to early and late extubation after cardiac surgery.